2018
DOI: 10.3389/fcimb.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Streptolysin S-Dependent and Independent Inflammatory Cytokine IL-1β Activity Reduces Pathology During Early Group A Streptococcal Skin Infection

Abstract: The bacterial pathogen Group A Streptococcus (GAS) has been shown to induce a variety of human diseases ranging in severity from pharyngitis to toxic shock syndrome and necrotizing fasciitis. GAS produces a powerful peptide toxin known as Streptolysin S (SLS). Though long recognized as a potent cytolysin, recent evidence from our lab has shown that SLS-dependent cytotoxicity is mediated through activation of the pro-inflammatory mediators p38 MAPK and NFκB. These findings led us to hypothesize that activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…According to our results, BBH + FLC, BBH alone and FLC alone reduce Rh6G excretion by decreasing CDR1 and CDR2 mRNA expression. Previous studies reported that Eucalyptal D ( Xu et al, 2019 ) geraniol ( Singh and Sharma, 2018 ) and magnolol ( Sun L. M. et al, 2015 ) which are substrates for Cdr1p efflux pumps, exert synergistic effects by simultaneously upregulating CDR1 and CDR2 expression, while competitively inhibiting FLC efflux. Numerous studies suggest that synergy results from increased intracellular drug accumulation caused by downregulated efflux pump genes in FLC-resistant strains ( Garcia-Gomes et al, 2012 ; Zhu et al, 2014 ; Shao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, BBH + FLC, BBH alone and FLC alone reduce Rh6G excretion by decreasing CDR1 and CDR2 mRNA expression. Previous studies reported that Eucalyptal D ( Xu et al, 2019 ) geraniol ( Singh and Sharma, 2018 ) and magnolol ( Sun L. M. et al, 2015 ) which are substrates for Cdr1p efflux pumps, exert synergistic effects by simultaneously upregulating CDR1 and CDR2 expression, while competitively inhibiting FLC efflux. Numerous studies suggest that synergy results from increased intracellular drug accumulation caused by downregulated efflux pump genes in FLC-resistant strains ( Garcia-Gomes et al, 2012 ; Zhu et al, 2014 ; Shao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the combined BBH and FLC effect on resistant C. albicans drug efflux, Rh6G assays were performed as previously described, with some modifications ( Xu et al, 2019 ). The cells were first incubated with constant shaking (200 rpm) in fresh RPMI 1640 at 35°C for 2 h to exhaust cellular energy stores.…”
Section: Methodsmentioning
confidence: 99%
“…Classically activated macrophages participate in key proinflammatory responses and enhance antigen presentation and pathogen clearance (Imai et al, 2018;Valderrama and Nizet, 2018;Hafner et al, 2019). IL-1β is a neutrophil recruitment factor produced by macrophages and DCs upon exposure to GAS (Valderrama et al, 2017;Flaherty et al, 2018;Liu et al, 2019). Recent research has discovered that an optimal level of IL-1β must be produced to eliminate pathogens and avoid excessive tissue lesion formation and mortality (Castiglia et al, 2016;Flaherty et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a neutrophil recruitment factor produced by macrophages and DCs upon exposure to GAS (Valderrama et al, 2017;Flaherty et al, 2018;Liu et al, 2019). Recent research has discovered that an optimal level of IL-1β must be produced to eliminate pathogens and avoid excessive tissue lesion formation and mortality (Castiglia et al, 2016;Flaherty et al, 2018). Thus, the survival of control mice producing inadequate amounts of these cytokines reduced because of impaired bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular bacteria and media were aspirated and the cells were washed with PBS and RPMI 1640 supplemented with 2% FBS, 100μg/ml gentamicin (Gibco), and 5μg/ml penicillin G (Sigma). The cells were incubated in 100nM PMA at 37°C with 5% CO 2 for 6 hrs prior to collecting the culture media for cytokine profiling as previously described 26 . The Abcam Human Cytokine Antibody Array Kit (ab133998), was performed according to the manufacturer's instructions with an Amersham Imager 600 (GE Life Sciences).…”
Section: Membrane-based Antibody Array For Detecting Cytokines In Thpmentioning
confidence: 99%